Food Insecurity Experience Scale (FIES) in Colombia, Guatemala, and México - Nathaly Garzón-Orjuela; Hugo Melgar-Quiñonez; Javier Eslava-Schmalbach (Instituto Nacional de Salud Pública, 2018)
Objetive. To compare the psychometric characteristics of the Food Insecurity Experience Scale (FIES) and the grade of similitude or difference among Colombia, Guatemala, and Mexico during three years. Materials and methods. Psychometric comparison using the Rasch model to calculate the relative severity of each item in FIES, INFIT and contrast in the Differential Functioning of Items (c-DIF). Results. The majority of items showed a relative severity corresponding to the theoretical construct and acceptably fit the model (INFIT=0.7-1.3). No c-DIF above 1.0 logit was observed in the comparison men vs women. In the comparison among countries by year 87% of the items showed c-DIF below 0.5 logit. Conclusion. The FIES presents psychometric characteristics corresponding to the theoretical construct of the tool. Future studies with the inclusion of more countries and more time points are essential to evaluate the relative severity, behavior and distribution of items.